(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Geriatric depression is emerging mental disorder with old age. The present study was carried out to estimate the prevalence of depression among residents of elderly homes in Eastern Nepal and to measure the severity of the symptoms of depressive disorders. Material And Method: This study involved residents of old age homes in four different districts of Eastern Nepal, the participants were heterogeneous with diverse cultural background and ethnicity. All elderly people of age 60 years and above living in the old age homes were at first informed about the rationale of our study, we took the informed verbal(as most of the subjects were illiterate) or written consent before going through our questionnaire which was translated into Nepali language by a panel of translators using repeated “forward backward procedure.” General Health questionnaire was applied to all subjects. Geriatric Depression scale (GDS) was then applied to those subjects whose score on GHQ-12 was ≥6 and the categorization of the subjects as normal, mild depressives or severe depressives was done. Results: A total of 62 elderly people of 60 years and above from aforementioned old age homes were enrolled in our study, out of which, 48.38% of the respondents belong to age group of 60-69 years , 27.4% belong to the age group 70-79 and 24.2 % were 80 years and above. Out of total respondents, 56.46% showed normal mental status on our GHQ scale while 43.54% were screened to have some sorts of psychological problems. The GDS detected them with mild and severe depressive symptoms. Out of which, 81.48% had mild depressive symptoms while 18.52% were severe depressive symptoms. Prevalence of depression was found to be significantly related to family history of mental illness. Conclusion: Most of the people living in the old age home in Eastern Nepal are found to have depressive symptoms among which majority have mild depressive symptoms and few have severe depressive symptoms. It depicts the miserable mental health of the elderly people in old age home.